Understanding Drivers of Coronavirus Disease 2019 Vaccine Hesitancy Among Blacks. (9th February 2021) - Momplaisir, Florence; Haynes, Norrisa; Nkwihoreze, Hervette; Nelson, Maria; Werner, Rachel M; Jemmott, John
Abstract: Background: Coronavirus disease 2019 (COVID-19) has disproportionately affected communities of color, with black persons experiencing the highest rates of disease severity and mortality. A vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has the potential to reduce the race mortality gap from COVID-19; however, hesitancy toward the vaccine in the black community threatens vaccine uptake. Methods: We conducted focus groups with black barbershop and salon owners living in zip codes of elevated COVID-19 prevalence to assess their attitudes, beliefs, and norms around a COVID-19 vaccine. We used a modified grounded theory approach to analyze the transcripts. Results: We completed 4 focus groups (N = 24 participants) in July and August 2020. Participants were an average age of 46 years, and 89% were black non-Hispanic. Hesitancy against the COVID-19 vaccine was high due to mistrust in the medical establishment, concerns with the accelerated timeline for vaccine development, limited data on short- and long-term side effects, and the political environment promoting racial injustice. Some participants were willing to consider the vaccine once the safety profile is robust and reassuring. Receiving a recommendation to take the vaccine from a trusted healthcare provider served as a facilitator. Health beliefs identified were similar to concerns around other vaccines and included the fear of getting the infection with vaccination and preferring to improve one's baseline physical health through alternative therapies. Conclusions: We found that hesitancy of receiving the COVID-19 vaccine was high; however, provider recommendation and transparency around the safety profile might help reduce this hesitancy. Abstract : In focus group discussions, hesitancy of a COVID-19 vaccine was high among black participants due to health beliefs against vaccines in general, compounded by skepticism of vaccine development during the pandemic and the political environment fostering racial injustice.